Regulation of endogenic metabolites by rosuvastatin in hyperlipidemia patients: An integration of metabolomics and lipidomics - Lee, Hyunbeom; Choi, Jong Min; Cho, Joo-Youn; Kim, Tae-Eun; Lee, Hwa Jeong; Jung, Byung Hwa (ELSEVIER IRELAND LTD, 2018)
Rosuvastatin is a statin used to treat metabolic syndrome conditions, such as hyperlipidemia. It is relatively safe; however, fatal rhabdomyolysis or skeletal myopathy can sometimes occur. Therefore, to investigate the overall effects of rosuvastatin, including lipid lowering and adverse effects, metabolic profiling was performed using metabolomics and lipidomics after rosuvastatin administration. Specifically, the metabolic profiles between healthy subjects and patients with hyperlipidemia were compared and the metabolic changes related to the mechanism of the drug effect were proposed. Healthy volunteers (n = 32) and hyperlipidemic patients (n = 14) were orally administered rosuvastatin (20 mg) once a day for 3-8 weeks, and plasma and urine were collected. Metabolomics and lipidomics were performed using UHPLC-LTQ/Orbitrap/MS/MS for non-targeted analysis and UHPLC-TQ-MS/MS for targeted analysis. Using non-targeted analysis, we successfully profiled and identified 73 and 87 metabolites in healthy subjects and hyperlipidemia subjects, respectively. Through targeted analysis, we have also quantified 188 metabolites, including amino acids, biogenic amines, glycerophospholipids, and sphingolipids. The levels of L-carnitine, diacylglycerol, and acylcarnitines significantly decreased after rosuvastatin administration regardless of the group. The overall levels of fatty acids (FA) and lysophosphatidylcholines (LysoPC) increased, while phosphatidylcholines (PC) decreased only in the patient group. beta-Oxidation decreased overall, while the production of polyunsaturated FA increased only in the hyperlipidemic patients. Using metabolic profiling, we have evaluated the alterations in the biochemical pathways, which may aid in a more detailed understanding of the effect of rosuvastatin. Patient-specific metabolomic and lipidomic profiles may serve as valuable markers for the understanding of the adverse effects associated with statin treatment.
Keywords: MITOCHONDRIAL DYSFUNCTION; PHOSPHOLIPASE A(2); MASS-SPECTROMETRY; OXIDATIVE STRESS; IDENTIFICATION; ATORVASTATIN; ASSOCIATION; BIOMARKERS; DRUGS